Infusing Religious Values for Enhanced Environmental Resilience: A Case Study of Pangalengan, Bandung Regency - M. Yusuf Wibisono; Muhtar Gojali (Prodi Magister Sosiologi UIN Sunan Gunung Djati Bandung, 2026)
The global environmental crisis and ecological degradation at the local level have become serious challenges to the sustainability of human life. In the Pangalengan area of Bandung Regency, pressure on the ecosystem occurs due to deforestation, agricultural land conversion, and declining water quality. In this context, a new approach is needed that combines local values and spiritual dimensions to strengthen environmental resilience. This article aims to explore the role of religion, particularly Islamic values, in fostering ecological awareness and collective community action through a community service model based on a transformative approach and Asset-Based Community Development(ABCD). This study uses a participatory qualitative approach with data collection techniques through participant observation, in-depth interviews, focus group discussions (FGDs), and community reflection. The results of the study indicate that the insertion of religious values—such as the concept of caliph, amar ma’ruf nahi denkar, and prohibition of waste—successfully triggered a transformation in public awareness of environmental issues. Thematic religious studies, mosque greening programs, and youth involvement as environmental cadres have spurred concrete and measurable action. Collaboration between religious leaders, village governments, and religious educational institutions has also resulted in a partnership model based on environmental spirituality. These findings demonstrate that religious values can serve as both an ethical foundation and a practical strategy in community-based environmental policies. The implications of this research underscore the need to integrate spiritual values, public policy, and ecological action to build sustainable environmental resilience at the local level.